(untitled) (Fiep Bulletin - online, 2017)
CONAF workers need to perform many tasks that demand own physical abilities to achieve them, because they run onnatural areas of mountains, forests, mountains, parks, etc. Objective: To self-perception, physical condition and feeding behaviorof workers CONAF, Maule Region, Talca, Curicó and Linares. Method: Quantitative approach, descriptive and non-experimentaldesign. They were assessed 46 officials (34 men and 12 women) from three units (Talca, Curicó and Linares), three datacollection instruments (IFIS, International Fitness Scale) were used; IPAQ, "International Physical Activity Questionnaire"; Shortversion of the Alimentary Behavior Survey. Assessments variables of fitness: cardiorespiratory endurance, strength (upper andlower limbs), speed, flexibility (upper and lower limbs and trunk, coordination). Results: Overall officials have less than optimal,indicated by the leaderboards for each test fitness. Linares officials are in better physical condition, followed by officials of thedepartments of Talca and finally officials Curicó units. Conclusion: The demands of work are superior to the physical conditionsthat workers present. They recognize that their physical condition is not ideal. Feeding and practicing physical activity are notadequate for health maintenance and quality of life. Proposals are needed to improve the worker’s physical condition and health.